The Enhancing Cooperation Capabilities in Utilizing Used Cartons as Educational Game Tools - Nurkhasyanah, Alfiyanti; Suyadi, Suyadi (Indonesian Journal of Early Childhood Education Studies, 2020)
This research is motivated by the interest of researchers in increasing the ability of cooperation in the use of used cardboard as an educational play tool in late childhood children in Canden Hamlet RT05, Canden, Jetis, Bantul, Yogyakarta. In general, this research is to find out the increase in the ability of children's cooperation in the use of used cardboard as an educational game tool. This research is a type of qualitative research that is descriptive in nature. Data obtained from the results of research using the method of collecting data observation, interviews, and documentation. While the technical analysis of the data used is data reduction, data presentation, and concluding. The results showed a significant increase in the ability of cooperation in the use of used cardboard as an educational game tool.